PELVIC LYMPHANEDECTOMY DUE TO METASTATIC BREAST CANCER CAUSING POSTRENAL ACUTE KIDNEY INJURY - Beloni, Ana Beatriz Charantola; Beloni, Ana Clara Charantola; Beloni, Leandro; Ferraz, Lúcio Fábio Caldas (Mastology, 2020)
Introduction: About 30% of the patients healed from breast cancer recurred with metastasis, and the lymphatic is the main path of dissemination. Usually, postrenal acute kidney failure (AKI) is a result of gynecological, urological, gastrointestinal and retroperitoneal cancer, but unusual in breast cancer. Objectives: To report the unusual metastatic behavior of the carcinoma for diagnostic elucidation. Method: Anamnesis and review of medical charts and bibliography. Results: White, female, 69-year old women being retreated for invasive ductal breast cancer, luminal B type, was hospitalized in June, 2018, with hypothesis of bronchopneumonia and AKI due to dehydration and infection. Laboratory examinations indicated urea at 75 mg/dl, creatinine at 2.56 mg/dl, sodium at 141 mmol/L, and potassium at 4.2 mmol/L. The initial con-duct included antibiotics and hydration with 0.9% saline solution. Abdominal and bladder ultrasound indicated dilata-tion of the pelvicalyceal systems system and proximal ureters, without pointing a location and cause of obstruction; uri-nary bladder with conserved shape and capacity; absence of images compatible with calculi and expansive solid, cystic or complex injuries. Due to the worsened glomerular filtration rate and oliguria, a double J catheter was inserted to the left. However, there was no improvement in kidney function. Then, a nephrostomy was performed to the right, which restitu-ted urine traffic. In February, 2019, urotomography showed dilatation of the pelvicalyceal system and right ureters to the pelvis (L5), where it became narrow, with a 1.5 cm caliber ureter obstruction; multiple metastasis in the pelvic bones and bilateral pleural effusion. A double J catheter was inserted in the right ureter through a cateter via anterograde pathway, thus recovering kidney function and comfort. After 5 months, computed tomography showed pelvic lymphadenopathy as the cause of obstruction. Currently, the patient has a metallic catheter in the right side, with good general status and on anastrozole. Conclusions: Metastatic breast cancer is still challenging and prone to complications. Therefore, its know-ledge allows a better approach of patients by correlating them with more diagnostic and care possibilities.